1998
DOI: 10.1099/00222615-47-12-1097
|View full text |Cite
|
Sign up to set email alerts
|

Different O and K Serotype Distributions among Clinical and Environmental Strains of Serratia Marcescens

Abstract: Recent revision of the 0 serotyping scheme for Serratia marcescens has allowed the definitive serological identification of a collection of 51 1 epidemiologically distinct strains in terms of both lipopolysaccharide (0) antigens and capsular (K) antigens. High levels of typability were achieved, 88% and 91y0 respectively, with only 2% failing to type with either method. In most cases, non-typability was due to a lack of antigen, i.e., the strains produced only rough LPS or were acapsular, suggesting that typab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In addition, as 19% of the clinical strains were from urine, 16% from blood and 14% from the respiratory tract [3], the data from these strains were analysed with respect to clinical source. However, no significant associations were found and therefore these results are not presented.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, as 19% of the clinical strains were from urine, 16% from blood and 14% from the respiratory tract [3], the data from these strains were analysed with respect to clinical source. However, no significant associations were found and therefore these results are not presented.…”
Section: Resultsmentioning
confidence: 99%
“…Most schemes are based on either the 0 antigens of lipopolysaccharide (LPS) or the K antigens of capsular polysaccharide. Recently, new 0 and K typing schemes have been described for this species [2], and applied to a collection of both clinical and environmental S. rnarcescens isolates selected to represent distinct strains [3]. The latter study showed a marked difference in serotype distribution between the two populations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations